Understanding basic statistics - Brase, Charles Henry; Brase, Corrinne Pellillo (Brooks/Cole, Cengage, 2013)
A condensed and more streamlined version of Brase and Brase's bestselling UNDERSTANDABLE STATISTICS, Tenth Edition, this book offers an effective way to learn the essentials of statistics, including early coverage of regression, within a more limited time frame. Designed to help learners overcome their apprehension about statistics, UNDERSTANDING BASIC STATISTICS, Sixth Edition, provides plenty of guidance and informal advice demonstrating the links between statistics and the real world. Thorough yet abbreviated, the text offers a reader-friendly style and a new, complete technology package to supplement learning. The use of the graphing calculator, Microsoft Excel, MINITAB, and SPSS is covered but not required